Chiral Nanoparticles with Enhanced Thermal Stability of Chiral Structures through Alloying. Issue 14 (17th February 2022) - Ma, Yicong; Lin, Chao; Cai, Linfeng; Qu, Geping; Bai, Xiaopeng; Yang, Lin; Huang, Zhifeng
Abstract: Metallic chiral nanoparticles (CNPs) promisingly function as asymmetric catalysts but lack an important study in thermal stability of optical activity that stems from metastable chiral lattices. In this work, annealing is applied to silver (Ag) CNPs, fabricated by glancing angle deposition (GLAD), and causes elimination of optical activity at 200 °C, mainly ascribed to chiral‐to‐achiral lattice transformation. The Ag CNPs are remarkedly enhanced in thermal stability through an alloying with aluminum (Al) via layer‐by‐layer GLAD to generate binary Ag0.5 Al0.5 CNPs composed of solid‐state liquids, whose optical activity vanishes at 700 °C. Ease in the diffusion of Al atoms in the host Ag CNPs and thermal insulation from the Al2 O3 layers partially covering the binary CNPs effectively prohibit structural relaxation of the metastable chiral lattices, accounting for the significant enhancement in thermal stability of chiral lattices. This is a pioneering work to investigate the fundamental principles determining the thermal stability of metallic CNPs in terms of chiral structures and optical activity. It paves the way toward applying metallic CNPs to asymmetric catalysis at high temperature to accelerate an asymmetric synthesis of enantiomers with designable chirality, which is one of the most important topics in modern chemistry. Abstract : Silver (Ag) chiral nanoparticles (CNPs), composed of metastable chiral lattices, completely lose optical activity by annealing at 200 °C. The vanishment of optical activity is remarkedly postponed to 700 °C by alloying the Ag CNPs with aluminum (Al), due to an ease of Al diffusion in the host Ag CNPs and thermal insulation of the Al2 O3 layers that effectively prohibit chiral‐to‐achiral relaxation of the metastable chiral lattices.